2023
DOI: 10.3390/diagnostics13101752
|View full text |Cite
|
Sign up to set email alerts
|

Review of Retinal Imaging Modalities for Hydroxychloroquine Retinopathy

Abstract: This review provides an overview of conventional and novel retinal imaging modalities for hydroxychloroquine (HCQ) retinopathy. HCQ retinopathy is a form of toxic retinopathy resulting from HCQ use for a variety of autoimmune diseases, such as rheumatoid arthritis and systemic lupus erythematosus. Each imaging modality detects a different aspect of HCQ retinopathy and shows a unique complement of structural changes. Conventionally, spectral-domain optical coherence tomography (SD-OCT), which shows loss or atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 144 publications
(207 reference statements)
0
0
0
Order By: Relevance
“…The feature maps demonstrate that the heatmap scores are predominantly concentrated around the foveal locations (F). This observation aligns with previous studies on HCQ retinal retinopathy, which have utilized OCT spectral-domain analysis [34][35][36][37][38][39]. These studies have indicated that the concentration and presence of HCQ active ingredients significantly impact the thickness in the corresponding area.…”
Section: A Novel Screening Technique For Hcq Retinopathysupporting
confidence: 90%
“…The feature maps demonstrate that the heatmap scores are predominantly concentrated around the foveal locations (F). This observation aligns with previous studies on HCQ retinal retinopathy, which have utilized OCT spectral-domain analysis [34][35][36][37][38][39]. These studies have indicated that the concentration and presence of HCQ active ingredients significantly impact the thickness in the corresponding area.…”
Section: A Novel Screening Technique For Hcq Retinopathysupporting
confidence: 90%